Microstructure versus topography: the impact of crystallographic substrate modification during ultrashort pulsed direct laser interference patterning on the antibacterial properties of Cu - Müller, Daniel Wyn; Josten, Ben; Wältermann, Sebastian; Pauly, Christoph; Slawik, Sebastian; Brix, Kristina; Kautenburger, Ralf; Mücklich, Frank (Frontiers in Materials, 2024)
Topographic surface patterning in the micro-and nanometer scale has evolved into a well applied approach in surface functionalization following biomimetic blueprints from nature. Depending on the production process an additional impact of process-related substrate modification has to be considered in functional surface optimization. This is especially true in case of antimicrobial applications of Cu surfaces where a modification of the substrate properties might impact bactericidal efficiency. In this regard, the effect of ultrashort pulsed direct laser interference patterning on the microstructure of pure Cu and resulting antimicrobial properties was investigated alongside line-like patterning in the scale of single bacterial cells. The process-induced microstructure modification was shown to play an important role in corrosion processes on Cu surfaces in saline environment, whereas the superficial microstructure impacts both corrosive interaction and ion emission. Surprisingly, antimicrobial efficiency is not predominantly following deviating trends in Cu ion release rates but rather depends on surface topography and wettability, which was shown to be impacted by the substrate microstructure state, as well. This highlights the need of an in-depth understanding on how different surface properties are simultaneously modulated during laser processing and how their interaction has to be designed to acquire an effective surface optimization e.g. to agitate active antimicrobial surface functionalization.